If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 3x * ln(3x) Multiply f * x fx = 3x * ln(3x) Remove parenthesis around (3x) fx = 3x * ln * 3x Reorder the terms for easier multiplication: fx = 3 * 3x * ln * x Multiply 3 * 3 fx = 9x * ln * x Multiply x * ln fx = 9lnx * x Multiply lnx * x fx = 9lnx2 Solving fx = 9lnx2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 9lnx Simplifying f = 9lnx
| 9x-136+6x-76=180 | | 12k-10k+4K+4K=20 | | 15=3/8w | | (5*x)/10=-7/(3*x) | | 2n^2+4n+6=4 | | 1/3÷5/6 | | m-6m+3m-5= | | 16x+260y=4 | | 5v/6=30 | | 11=4x+3(2.75) | | 12k-10k+4K=20 | | 3n^2=-6 | | 10-X=2/3 | | 16g-15g=13 | | 27x^2+5=48 | | 30/x=5/2 | | 16g-14g=8 | | -6(6s+5)= | | 1/2/3=x/2/3 | | (5*x)/10=-(7/3)x | | 30+15+.65x=35+35+.75 | | x/2-4=22 | | f(x)=1-4x-5x^4 | | -x+156=26 | | 19k+k=20 | | m=42 | | 5x+15x-4=4(5x+3) | | 219-x=157 | | 11=5x+3(2.75) | | 6x+(2x-y)= | | 5x/10=-7/3x | | 9(x-15)=405 |